Array-based sensing of explosives by water-soluble poly(p-phenyleneethynylene)s - Wang, Benhua; Han, Jinsong; Bender, Markus; Seehafer, Kai; Bunz, Uwe H. F. (Macromolecules, 2017)
We have prepared four water-soluble poly(p-phenyleneethynylene)s, two of which are novel and carry benzylic side chains that are negatively charged. All of the four PPEs were employed to detect nitroaromatic compounds in water. The two novel PPEs with the benzylic side chains react fairly sensitive toward DNT and TNT in water. If the benzylic side groups are alkoxy-substituted, TNT is detected at concentrations down to 0.27 μM. 12 different nitroaromatics were successfully discriminated by a small array consisting of either two or four of the PPEs and employing linear discriminant analysis.